An Outbreak of Vancomycin-Resistant Enterococcus faecium in an Acute Care Pediatric Hospital: Lessons from Environmental Screening and a Case-Control Study. Issue 3 (2008) - Drews, Steven J; Richardson, Susan E; Wray, Rick; Freeman, Renee; Goldman, Carol; Streitenberger, Laurie; Stevens, Derek; Goia, Cristina; Kovach, Danuta; Brophy, Jason; Matlow, Anne G
Abstract : BACKGROUND: The present study describes a vancomycin-resistant enterococci (VRE) outbreak investigation and a case-control study to identify risk factors for VRE acquisition in a tertiary care pediatric hospital. OBJECTIVE: To report an outbreak investigation and a case-control study to identify risk factors for VRE colonization or infection in hospitalized children. METHODS: Screening for VRE cases was performed by culture or polymerase chain reaction. A case-control study of VRE-colonized patients was undertaken. Environmental screening was performed using standard culture and susceptibility methods, with pulsed-field gel electrophoresis to determine relationships between VRE isolates. Statistical analysis was performed using SAS version 9.0 (SAS Institute Inc, USA). RESULTS: Thirty-four VRE-positive cases were identified on 10 wards between February 28, 2005, and May 27, 2005. Pulsed-field gel electrophoresis analysis confirmed a single outbreak strain that was also isolated from a video game found on one affected ward. Multivariate analysis identified cephalosporin use as the major risk factor for VRE colonization. CONCLUSIONS: In the present study outbreak, VRE colonization was significantly associated with cephalosporin use. Because shared recreational items and environmental surfaces may be colonized by VRE, they warrant particular attention in housekeeping protocols, particularly in pediatric institutions.